Ta có: [TEX]\widehat{MHC}=90^0-\widehat{CHQ}=90^0-\widehat{PHF}=\widehat{APH}[/TEX]
Lại có [TEX]\widehat{PAH}=\widehat{HCD}[/TEX] ( cùng phụ [TEX]\widehat{ABC}[/TEX] )
Do đó tam giác AHP đồng dạng tam giác CMH [TEX]\rightarrow \frac{HP}{HM}=\frac{AH}{CM}=\frac{2AH}{BC}[/TEX]
Chứng minh tương tự ta có tam giác AHQ đồng dạng tam giác BMH [TEX]\rightarrow \frac{HQ}{HM}=\frac{AH}{BM}=\frac{2AH}{BC}[/TEX]
[TEX]\rightarrow \frac{HP}{CM}=\frac{HQ}{HM} \leftrightarrow HP=HQ \rightarrow[/TEX] H là trung điểm PQ.